Tectona Grandis seed powder and Mangifera Indica leaf powder as bio adsorbents for removal of methylene blue from aqueous solution - Divya N. Shetty; Vinola A. Lobo; Suman Rani; Narasimha Raghavendra (Hybrid Advances)
This study intends to describe the use of modified Tectona Grandis seed powder (TG) and Mangifera Indica leaf powder (MI) as adsorbent materials in the process of removing Methylene Blue (MB) from the wastewater. Nitric acid (HNO3) was used to chemically modify the plant material. Thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and X-ray diffraction (XRD) were utilized to analyze the modified bio adsorbents (TG and MI). The adsorbents' ideal specific surface area and pore volume were measured using the N2 adsorption/desorption technique through detailed characterization. The efficiency of the adsorbents in eliminating the MB dye was investigated in relation to the effects of adsorbent dose (2–10 mg), pH (3, 7 and 10), exposure time (10–90 min), temperature (30 °C, 50 °C and 70 °C), and dye concentration (20–100 mg/L) through batch adsorption studies. The models proposed by Langmuir, Freundlich, and Dubinin Raduskevich (D-R) could explain the binding results for MB on TG and MI. The adsorption process were more in line with the Langmuir model than the other models. At neutral pH (7), TG showed maximum percentage removal of 73.12 % whereas, MI powder showed a maximum percentage removal of 50.5 %. Time and adsorbent dosage have both led to an increase in the percentage of methylene blue elimination. The experimental results were confirmed by density functional theory (DFT) calculations, which revealed energy gaps (ΔE) of 4.57 eV and 7.882 eV for MB and TG/MI, respectively. Following complexation, a change of 16.56 eV was observed, indicating a stronger MB adsorption tendency across the modified TG/MI surface. The primary components of the mechanism of MB adsorption include hydrogen bonds, n-π, π-π, and electrostatic interactions, as per the results of Monte Carlo (MC) simulation calculations. According to our findings, TG and MI are affordable biomaterials for treating wastewater in an ecologically responsible and green manner.